2019
DOI: 10.1007/s40264-019-00848-9
|View full text |Cite|
|
Sign up to set email alerts
|

Patient Registries: An Underused Resource for Medicines Evaluation

Abstract: IntroductionPatient registries, ‘organised systems that use observational methods to collect uniform data on a population defined by a particular disease, condition, or exposure, and that is followed over time’, are potentially valuable sources of data for supporting regulatory decision-making, especially for products to treat rare diseases. Nevertheless, patient registries are greatly underused in regulatory assessments. Reasons include heterogeneity in registry design and in the data collected, even across r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 65 publications
(25 citation statements)
references
References 13 publications
2
22
0
Order By: Relevance
“…There are additional opportunities for HTA bodies and regulatory agencies engagement around optimization of realworld data (RWD) generation such as the use of patient registries (98) or the opportunity to share periodic benefit-risk assessment reports and therapeutic value reassessments. This would include alignment on key areas such as outlining the definition of data to be collected (i.e., minimum dataset) in registries (19).…”
Section: Post-authorization Data/evidence Generationmentioning
confidence: 99%
“…There are additional opportunities for HTA bodies and regulatory agencies engagement around optimization of realworld data (RWD) generation such as the use of patient registries (98) or the opportunity to share periodic benefit-risk assessment reports and therapeutic value reassessments. This would include alignment on key areas such as outlining the definition of data to be collected (i.e., minimum dataset) in registries (19).…”
Section: Post-authorization Data/evidence Generationmentioning
confidence: 99%
“…However, a recent paper has demonstrated that patient registries are still very much underused for regulatory decisions, suggesting a set of operational proposals to increase their use. 13 In fact, it must be recognized that not all registries have the same quality, level of detail, or even reliability and that needs to be carefully considered before embarking on decisions that assume registry data are unquestionable.…”
Section: Variability and Quality Of Registriesmentioning
confidence: 99%
“…They are organised systems that use observational methods to collect consistent data on a population defi ned by a particular disease, condition or exposure, which is followed over time 18 . They provide a precise, systematic and structured collection of relevant data 19 . A key element is their longitudinal projection over time.…”
Section: Adaptation Number 3: Studies On Safety and Effectiveness To mentioning
confidence: 99%
“…Regulatory Agencies have begun facilitation of some of these aspects. EMA established in 2015 the Patient Registries Initiative, to support registries in collecting data suitable to contribute to regulatory assessments, especially post-authorization safety and effi cacy studies 19 . These initiatives take time to produce results, and some challenges, such as the heterogeneity of data, privacy issues, and data ownership are notoriously diffi cult to overcome, but there are concerted efforts to increase their use in regulatory decision making.…”
Section: Adaptation Number 3: Studies On Safety and Effectiveness To mentioning
confidence: 99%